Optimal Hybrid Fuzzy PID for Pitch Angle Controller in Horizontal AxisWind Turbines - Adnan, Adnan; Hussain, Mohammed (Iraqi Journal for Electrical and Electronic Engineering, 2025)
Wind turbine (WT) is now a major renewable energy resource used in the modern world. One of the most significanttechnologies that use the wind speed (WS) to generate electric power is the horizontal-axis wind turbine. In order toenhance the output power over the rated WS, the blade pitch angle (BPA) is controlled and adjusted in WT. This paperproposes and compares three different controllers of BPA for a 500-kw WT. A PID controller (PIDC), a fuzzy logiccontroller (FLC) based on Mamdani and Sugeno fuzzy inference systems (FIS), and a hybrid fuzzy-PID controller(HFPIDC) have been applied and compared. Furthermore, Genetic Algorithm (GA) and Particle swarm optimization(PSO) have been applied and compared in order to identify the optimal PID parameters (kp, ki, kd). The objective of GAand PSO is minimized the error signal in output power based on actual WS. The results for three different controllersshow that the optimal hybrid FPIDC based on the Sugeno inference system with PSO produces the optimal results regardto reduce the error signal and stable output power under actual WS.